Legal Protection for Nurses in Non Civil Servants in Health Centers in Langgudu Sub-District Bima Regency After the Enactment of Law Number 38 the Year 2014 Concerning Nursing - Al Muhajirin; Tjahjono Kuntjoro; Yovita Indrayati (SOEPRA, 2018)
Local Government Clinic in Langgudu Subdistrict, Bima Regency, is one of the Government institutions that employ health and non-health workers. One of the health workers themselves is nurses. Nurses who practiced at the clinic have recruited both nurses who have the status of civil servants, impermanent officers, and voluntary nurses. The voluntary nurses who were recruited and appointed by the head of the clinic. On the other hand, the recruitment in the local government should comply with the legislation of the state civil apparatus. As the recruitment is not by the legislation of the state civil apparatus, it will have an impact on the legal protection for the nurses in a local government clinic.                 This research was done at a clinic in Langgudu subdistrict of Bima Regency using sociology juridical research method. The specification of the research was descriptive analytic using primary and secondary data. Data collection techniques used in the research was face to face interview, question draft distribution, and interview by phone. The Information or resource of this research was the head of the health official, heads of clinics in Langgudu subdistrict and the chairman of Indonesian National Nurses Organization of Bima Regency. Then, The respondents were the nurses who work at the clinic in Langgudu Subdistrict, either nurse who have the status of civil servant, local honorary workers or the voluntary nurses.                The research result found that the regulation of employee appointment to work in a government institution was set in regent’s regulation number 15A about appointment guideline, placement, Dismissal, and honorary workers discipline of local government. In the regulation, the person who has authority in appointing the employees is the regent as the builder of the officers. In implementing of the regulation the head of the Clinic appointsnurse workers by himself to employ at the clinic. Thus, such things have already broken authority as leader of the institution in the sphere of local government as it is not by the rules of the Regent of Bima. Therefore, such appointments an obstacle in giving protection for voluntary Nurses because the process of appointment is not appropriate and breaking authority. As a head of clinics is not given authority and should not recruit or appoint the workers to employ at government institutions. The appointment of the workers shows that understanding of heads of clinics about management of the worker appointment at the clinics still lack, in addition to the absence of legislation regulations managing the volunteers so that it is an obstacle in providing legal protection for voluntary nurses who work in a clinic.